Biochar produced from biosolids using a single-mode microwave: Characterisation and its potential for phosphorus removal. (1st July 2017) - Antunes, Elsa; Schumann, James; Brodie, Graham; Jacob, Mohan V.; Schneider, Philip A.
Abstract: The amount of biosolids increases every year, and social and environmental concerns are also rising due to heavy metals and pathogen contamination. Even though biosolids are considered as a waste material, they could be used as a precursor in several applications, especially in agriculture due to the presence of essential nutrients. Microwave assisted pyrolysis (MWAP) is a promising technology to safely manage biosolids, while producing value-added products, such as biochar, that can be used to improve soil fertility. This study examined the impact of pyrolysis temperature between 300 °C and 800 °C on the chemical and physical properties of biochar obtained from biosolids via MWAP. Preliminary phosphorus adsorption tests were carried out with the biochar produced from biosolids. This research demonstrated that pyrolysis temperature affects biochar specific surface area, ash and volatiles content, but does not impact heavily on the pH, chemical composition and crystalline phases of the resultant biochar. Biochar yield decreases as the pyrolysis temperature increases. Phosphorus adsorption capacity of biochar was approximately around 15 mg/g of biochar. Biochar resulting from MWAP is a potential candidate for land application with an important role in water and nutrient retention, due to the high surface area. Highlights: Biochar yield decreases 15% when the pyrolysis temperature increases from 300 °C to 800 °C. Pyrolysis temperature affects significantly biochar surface area. Inorganic elements are concentrated in biochar, no volatilisation was observed with increase of pyrolysis temperature. Phosphorus removal capacity of biochar was approximately 15 mg/g of biochar.